Pond Productivity and Water Quality in Various Vaname Shrimp (Litopenaeus vannamei) Farming Systems at BPBAP Ujong Batee Aceh Besar - Muhammad Muhammad; Muyassir Muyassir; Muhammadar Muhammadar (Rona Teknik Pertanian, 2022)
Abstract. Traditional shrimp farming systems are generally susceptible to disease outbreaks, resulting in low productivity. However, the application of farming technology can reduce these risks. This study aims to calculate the production and examine pond water quality in vannamei shrimp culture by applying semi-intensive, intensive, and super-intensive farming systems through direct measurements and field observations. The results showed that the highest productivity was produced in super-intensive ponds at 5.4 kg/m2, in intensive systems at 2,325 kg/m2, and in semi-intensive farming systems at 0.575 kg/m2. The semi-intensive salinity ranged from 30.8 ppt to 35.1 ppt, the super-intensive salinity ranged from 29.2 to 31.9 ppt, and the semi-intensive salinity ranged from 30.9 to 34.2 ppt. The temperature ranges from 26.7 to 28.5°C for semi-intensive culture, 25.9 to 28°C for super-intensive farming, and 27.8 to 29.3°C for semi-intensive farming. The pH in the semi-intensive farming system is 7.9-8.3, the super-intensive pH is 7.7-8.6, and the semi-intensive system is at pH 7.7-8.2. Dissolved oxygen levels range from 4.0 to 5.9 ppm in intensive shrimp farming, 3.0 to 3.6 ppm in super-intensive shrimp farming, and 3.2 to 4.0 ppm in semi-intensive shrimp farming. Therefore, it can be concluded that the higher the farming technology applied, the higher the ponds' productivity. Meanwhile, differences in farming systems do not impact changes in water quality.Abstrak. Budidaya udang sistem tradisional mudah terjadi penyebaran penyakit dan produksinya rendah. Penerapan teknologi budidaya dapat mengurangi resiko. Penelitian ini bertujuan untuk mengukur produksi dan menganalisa kualitas air tambak pada budidaya udang vaname dengan menerapkan metode budidaya semi intensif, intensif dan super intensif melalui pengukuran secara langsung dan observasi di lapangan. Hasil penelitian menunjukkan produktivitas tertinggi dihasilkan pada kolam super intensif sebesar 5,4 kg/m2, pada metode intensif  2,325 kg/m2 dan pada metode budidaya semi intensif 0,575 kg/m2. Parameter kualitas air pada semi intensif salinitas berada pada level 30,8 ppt - 35,1‰, super intensif salinitas 29,2-31,9‰ dan pada semi intensif salinitas 30,9-34,2‰. Suhu pada metode budidaya semi intensif berada pada level 26,7-28,5°C.  pada  super intensif 25,9-28°C dan  pada metode semi intensif 27,8-29,3°C. pH pada metode budidaya semi intensif berada pada level 7,9-8,3 super intensif pH 7,7-8,6 dan metode semi intensif pH 7,7-8,2. Oksigen terlarut pada metode budidaya udang intensif 4.0-5,9 ppm, pada super intensif oksigen terlarut 3.0-3,6 ppm dan semi intensif 3,2-4,0 ppm. Dapat disimpulkan semakin tinggi teknologi budidaya yang diterapkan akan berdampak pada semakin tingginya produktivitas tambak yang dihasilkan. Perbedaan metode budidaya tidak berdampak pada perubahan kualitas air atau ketiga metode budidaya tersebut berdampak yang sama terhadap kualitas air.